Lignum Vitae (Guaiacum Officinale) - Freeman, Mrs. W.C. (My University, 2009)
A painting of the Lignum Vitae (Guaiacum officinale). A description on the back of the postcard reads: "The Lignum Vitae (Guaiacum officinale) is a small evergreen tree native to Trinidad and Tobago. Its wood is extremely hard. When in flower it is very beautiful; the flowers are violet when freshly open, fading to almost white."
Colour: Coloured; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Guaiacum (Genus); Plants--Trinidad and Tobago; Plants, Ornamental--Trinidad and Tobago